ЯЗЫК СТИХОТВОРЕНИЙ РУССКИХ ЗАКЛЮЧЁННЫХ КАК СВОЕОБРАЗНЫЙ СОЦИОЛИНГВИСТИЧЕСКИЙ ДОКУМЕНТ ТЮРЕМНОЙ ДЕЙСТВИТЕЛЬНОСТИ 80-90-ЫХ ГГ. ХХ ВЕКА - Gojło, Beata (Acta Neophilologica, 2007)
The starting point for the considering were selected works collected by Luba Nebreniczna. The analysis involves description of the language mechanisms that appear on the way of reflecting the inprisonment reality in the poems. There are considered functions of the poems’ language and criminal argot importance for the culture. There are also discussed and characterized: stylistic, semantic, artistic way of expression, foreign words presence (taken from the dialects and colloquial speech). Usage of epithets, methaphors and comparisons is pointed out; rhymes and lines systems are described.